A case report of Lemierre's Syndrome associated with dental sepsis. Issue 1 (February 2013) - Boyd, D; Paterson, P; Dunphy, L; Carton, A; Hammersley, N
Introduction: Lemierre's syndrome is a potentially fatal condition characterised by spread of an oropharyngeal infection, resulting in thrombosis of the internal jugular vein. This leads to septicaemia and possible metastatic abscesses. Case presentation: We discuss the case of a previously healthy 17-year-old male who developed Lemierre's syndrome following dental sepsis. He presented with bilateral submandibular and submental swelling extending into the neck and chest. His management included a tracheostomy; incision and drainage of the abscesses; drainage of a pleural effusion and prolonged anticoagulant therapy. Conclusion: The incidence of Lemierre's disease appears to be increasing and early diagnosis is essential. A high index of suspicion is needed in cases of oropharyngeal infection followed by fever, tender swelling of the neck and dysphagia – especially in young patients.